2016
DOI: 10.1590/0103-6440201600604
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Seal of Two Types of Tapered Implant Connections

Abstract: Tapered implant connections have gained wide popularity for being more resistant to fatigue and for promoting a better seal against bacterial infiltration than conventional connections. The aim of this study was to evaluate the bacterial seal at the implantabutment interface using two Morse taper implant models, by in vitro microbiological analysis. Eleven non-indexed and 11 indexed abutments were selected and connected to their respective implants with a 20 N torque, according to manufacturer's recommendation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 13 publications
0
17
0
1
Order By: Relevance
“…Additionally, the external hexagon determines the rotational position 15 . Alternatively, the morse taper connection has gained wide popularity for being more resistant to fatigue and for promoting a better seal against bacterial infiltration when considering conventional connections 16 , with sealing and friction principles. The morse taper has a design in which a cone with an angulation between 2 and 4 degrees is embedded in another cone by friction, without the need for screws, creating a cold weld between the parts, promoting greater resistance to displacement by axial and lateral forces and higher resistance to rotational movements 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the external hexagon determines the rotational position 15 . Alternatively, the morse taper connection has gained wide popularity for being more resistant to fatigue and for promoting a better seal against bacterial infiltration when considering conventional connections 16 , with sealing and friction principles. The morse taper has a design in which a cone with an angulation between 2 and 4 degrees is embedded in another cone by friction, without the need for screws, creating a cold weld between the parts, promoting greater resistance to displacement by axial and lateral forces and higher resistance to rotational movements 17 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been regarded as a safe, reliable and also an important factor for the maintenance of bone crest, due to microgap reduction and reduced risk of bacterial contamination. Some studies that used different conical fitting systems have, however, demonstrated bacterial leakage through such interface [3, 5, 8, 10, 15]. …”
Section: Discussionmentioning
confidence: 99%
“…Twelve sets of indexed tapered connection components and twelve sets of external hexagon connection components were used (Figure 1) for microbiological analysis as previously described [10]. For each model, an implant with its respective prosthetic abutment was used as a negative control and a set without the abutment as a positive control of microbial contamination.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Implant systems differ from each other in the geometry of the implant / abutment interface, especially between tapered and hexagonal connections. Such interface is the most vulnerable point of the entire implant-supported restoration, as it must resist constant masticatory forces as well bacterial invasion (Alves et al, 2014).…”
Section: Introductionmentioning
confidence: 99%